Platforms, advances, and technical challenges in virus-like particles-based vaccines - Gupta, Reeshu; Arora, Kajal; Roy, Sourav Singha; Joseph, Abyson; Rastogi, Ruchir; Arora, Nupur Mehrotra; Kundu, Prabuddha K. (Frontiers in Immunology, 2023)
Viral infectious diseases threaten human health and global stability. Several vaccine platforms, such as DNA, mRNA, recombinant viral vectors, and virus-like particle-based vaccines have been developed to counter these viral infectious diseases. Virus-like particles (VLP) are considered real, present, licensed and successful vaccines against prevalent and emergent diseases due to their non-infectious nature, structural similarity with viruses, and high immunogenicity. However, only a few VLP-based vaccines have been commercialized, and the others are either in the clinical or preclinical phases. Notably, despite success in the preclinical phase, many vaccines are still struggling with small-scale fundamental research owing to technical difficulties. Successful production of VLP-based vaccines on a commercial scale requires a suitable platform and culture mode for large-scale production, optimization of transduction-related parameters, upstream and downstream processing, and monitoring of product quality at each step. In this review article, we focus on the advantages and disadvantages of various VLP-producing platforms, recent advances and technical challenges in VLP production, and the current status of VLP-based vaccine candidates at commercial, preclinical, and clinical levels.